Neisseria meningitidis serogroup B carriage by adolescents and young adults living in Milan, Italy: Prevalence of strains potentially covered by the presently available meningococcal B vaccines - Leonardo Terranova; Nicola Principi; Sonia Bianchini; Giada Di Pietro; Giulia Umbrello; Barbara Madini; Susanna Esposito (Human Vaccines & Immunotherapeutics, 2018)
Recently, two vaccines against meningococcal serogroup B (MenB) have been developed. They are prepared according to the reverse vaccinology approach and contain 4 (4CMenB) and 2 (MenB-FHbp) cross-reactive surface proteins. In Italy 4CMenB vaccine has been included in the official vaccination schedule only recently and recommended only for infants and toddlers, whereas MenB-FHbp is not licensed. In order to collect information about the present carriage of Neisseria meningitidis serogroup B (MenB) in Italian adolescents and to evaluate the potential protection offered by the presently available MenB vaccines, 2,560 otherwise healthy, high school students aged 14–21 years (907 males, 35.4%, median age 16.2 years) were enrolled in Milan, Italy. A swab to collect posterior pharynx secretions was collected from each subject and meningococcal identification, serogrouping, multilocus sequence typing analysis, sequence alignments and phylogenetic analysis were performed. A total of 135 (5.3%) adolescents were meningococcal carriers. Strains belonging to serogroup B were the most common (n = 58; 2.3%), followed by MenY (n = 32; 1.2%), MenC (n = 7; 0.3%), MenW (n = 6; 0.3%) and MenX (n = 5; 0.2%). The remaining bacteria were not capsulated. The identified MenB strains belonged to eleven clonal complexes (CCs): ST-162 CC (n = 12; 20.7%), ST-865 CC (n = 12; 20.7%), ST-41/44/Lin.3 CC (n = 11; 19.0%), ST-35 CC (n = 6; 10.3%), ST-32/ET-5 CC (n = 4; 6.9%), ST-269 CC (n = 3; 5.2%), ST-213 CC (n = 2; 3.4%), ST-198 CC (n = 1; 1.7%), ST-461 CC (n = 1; 1.7%), ST-549 CC (n = 1; 1.7%), and ST-750 CC (n = 1; 1.7%). This study showed that MenB was the most commonly carried meningococcal serogroup found in adolescents living in Milan, Italy. The MenB vaccines presently licensed could have theoretically induced the production of antibodies effective against the greatest part of the identified MenB strains (100% in the case of 4CMenB and 95% in case of MenB-FHbp) Monitoring carriage remains essential to evaluate MenB circulation, but further studies are necessary to evaluate the effect on carriage and the final efficacy of both new MenB vaccines.